(untitled) (Jurnal Bahasa, 2023)
Deixis refers to how a language is uttered and how its utterance completes the context of what is said (Levinson, 1983). Studies of deixis in film are scarce and not widely explored because they are more focused on the corpus of advertisements and language or dialect. Based on observation, at present, there is still no research by local scholars that concentrate on deictic elements in film. Thus, the objective of this study is to identify the types of deixes in the film ’Hikayat Merong Mahawangsa’ and analyze the deixes found based on the utterances in the said film. This study uses literature review and textual analysis methods in the data collection based on the framework of Levinson’s Pragmatics Theory (1983). The findings were identified and categorized into the five types of deixes outlined in Levinson’s Pragmatics Theory, which are the person deixis, time deixis, place deixis, social deixis and discourse deixis. This study will assist in broadening the scope of deixis studies and further increase the turnout of research on deixis. Clearly, the use of deixis can indirectly provide an overview of an event, such as the use of spatial, time and discourse deixis. The use of deixis can also provide clear information about a matter to be conveyed. Keywords: Usage, deixis, pragmatics, Levinson, film, Hikayat Merong Mahawangsa Full text: PDF